How Sports Began - Oram, Sandie (Macdonald and Company (Publishers) Ltd, 1972)
Starters Long Ago books are vocabulary controlled books designed to stimulate interest in the young child in simple topics from history.
Keywords: Historical- How Sports Began; Juvenile Fiction